Scaffolding Process Based on Error Analysis in Solving the Problem: Second Order Differential Equation - Noor, Naili Luma'ati (Jurnal Pendidikan Matematika, 2022)
Error analysis in solving mathematics problems is needed to be done so that the lecturer and the students can find out the students’ error in solving the problems. So, in the future the lecturer will administer the more appropriate scaffolding. The aim of this research is to analyze the appropriate scaffolding administered for the students based on error identification according to the Newman procedure of the students in solving second order differential equation. The method of this research was qualitative research case study design. The subject of the research was the students of mathematics education study program at IAIN Kudus who took differential equation class in the first semester in the academic year 2021/2022. The technique for data collection used were test and interview techniques. The result of the research of scaffolding administered for the students was by the techniques of inviting student participation, the students who performed comprehension errors obtained scaffolding in the form of offering explanations and verifying and clarifying student understandings, the students who performed transformation errors obtained offering explanations and modeling of desired behaviors techniques, the students who performed process skill errors obtained scaffolding in the form of Inviting students to contribute clues and Inviting student techniques, and the students who performed encoding errors obtained scaffolding in the form of Inviting student participation. Analisis kesalahan dalam menyelesaikan masalah matematika perlu dilakukan agar dosen dan mahasiswa dapat mengetahui kesalahan mahasiswa dalam menyelesaikan masalah. Jadi, kedepannya dosen akan mengelola scaffolding yang lebih tepat. Penelitian ini bertujuan untuk menganalisis scaffolding yang tepat diberikan kepada siswa berdasarkan identifikasi kesalahan menurut prosedur Newman siswa dalam menyelesaikan persamaan diferensial orde dua. Metode penelitian ini adalah penelitian kualitatif dengan desain studi kasus. Subyek penelitian ini adalah mahasiswa program studi pendidikan matematika di IAIN Kudus yang mengambil mata kuliah persamaan diferensial pada semester I tahun ajaran 2021/2022. Teknik pengumpulan data yang digunakan adalah teknik tes dan wawancara. Hasil penelitian scaffolding yang diberikan kepada siswa adalah dengan teknik mengundang partisipasi siswa, siswa yang melakukan kesalahan pemahaman memperoleh scaffolding berupa menawarkan penjelasan dan memverifikasi dan memperjelas pemahaman siswa, siswa yang melakukan kesalahan transformasi memperoleh penjelasan menawarkan dan teknik pemodelan perilaku yang diinginkan, siswa yang melakukan kesalahan keterampilan proses memperoleh scaffolding berupa mengundang siswa untuk menyumbangkan petunjuk dan teknik Mengundang siswa, dan siswa yang melakukan kesalahan encoding memperoleh scaffolding berupa mengundang partisipasi siswa.